The levels of serum chemokines in patients with Behçet's disease - Kökçam, İbrahim; Turgut, Dilara; Ilhan, Fulya; Çiçek, Demet (My University, 2012)
Aim: As chemokines are involved in the regulation of immune responses and infl ammatory reactions, this study aimed to investigate the serum levels of some chemokines to determine whether they play roles in the pathogenesis of Behçet s disease (BD). Materials and methods: The study comprised 64 cases, allocated to active or inactive patient groups. The levels of serum macrophage inflammatory protein-1α (MIP-1α), epithelial neutrophil-activating protein-78 (ENA-78), and neutrophilactivating peptide-2 (NAP-2) were measured. Results: The serum levels of MIP-1α and ENA-78 were statistically higher in BD patients than controls (P = 0.032 and P = 0.023, respectively). However, NAP-2 levels did not differ significantly between patients and controls (P > 0.05). A significantly higher mean serum level of ENA-78 was found in patients with active disease compared to patients with inactive disease and controls (P = 0.029 and P = 0.003, respectively). However, mean serum MIP-1α and NAP-2 levels did not differ significantly between active and inactive patients (P > 0.05). Conclusion: In this study, there was a significant elevation of MIP-1α and ENA-78 supporting the role of neutrophil hyperactivity in BD. However, because chemokines insert their eff ects in the microenvironment and serum concentrations reflect a developing inflammatory process indirectly, we suggest that more comprehensive studies are needed to reveal the role of chemokines in the pathogenesis of the disease.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp